(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Yezhova O. V. Setting out requirements for the personality qualities of a skilled worker. The article is aimed at establishing a scientifically substantiated list of personality traits necessary for the successful forming professional competences of garment workers. The author determined that people of these occupations require such qualities as «person-to-technique» and for some tasks – «person-to-person» and «person-to-artistic image». This list includes 39 professionally important qualities; the list was reduced to 33 qualities as a result of a priori ranking.